The Targeted SMAC Mimetic SW IV-134 is a strong enhancer of standard chemotherapy in pancreatic cancer. Issue 1 (December 2017) - Hashim, Yassar; Vangveravong, Suwanna; Sankpal, Narendra; Binder, Pratibha; Liu, Jingxia; Goedegebuure, S.; Mach, Robert; Spitzer, Dirk; Hawkins, William
Abstract Background Pancreatic cancer is a lethal malignancy that frequently acquires resistance to conventional chemotherapies often associated with overexpression of inhibitors of apoptosis proteins (IAPs). We have recently described a novel means to deliver second mitochondria-derived activator of caspases (SMAC) mimetics selectively to cancer cells employing the sigma-2 ligand/receptor interaction. The intrinsic death pathway agonist SMAC offers an excellent opportunity to counteract the anti-apoptotic activity of IAPs. SMAC mimetics have been used to sensitize several cancer types to chemotherapeutic agents but cancer-selective delivery and appropriate cellular localization have not yet been considered. In our current study, we tested the ability of the sigma-2/SMAC drug conjugate SW IV-134 to sensitize pancreatic cancer cells to gemcitabine. Methods Using the targeted SMAC mimetic SW IV-134, inhibition of the X-linked inhibitor of apoptosis proteins (XIAP) was induced pharmacologically and its impact on cell viability was studied alone and in combination with gemcitabine. Pathway analyses were performed by assessing caspase activation, PARP cleavage and membrane blebbing (Annexin-V), key components of apoptotic cell death. Single-agent treatment regimens were compared with combination therapy in a preclinical mouse model of pancreatic cancer. Results The sensitizing effect of XIAP interference toward gemcitabine was confirmed via pharmacological intervention using our recently designed, targeted SMAC mimetic SW IV-134 across a wide range of commonly used pancreatic cancer cell lines at concentrations where the individual drugs showed only minimal activity. On a mechanistic level, we identified involvement of key components of the apoptosis machinery during cell death execution. Furthermore, combination therapy proved superior in decreasing the tumor burden and extending the lives of the animals in a preclinical mouse model of pancreatic cancer. Conclusion We believe that the strong sensitizing capacity of SW IV-134 in combination with clinically relevant doses of gemcitabine represents a promising treatment option that warrants clinical evaluation.